Modeling the heterogeneity of sodium and calcium homeostasis between cortical and hippocampal astrocytes and its impact on bioenergetics - Thapaliya, Pawan; Pape, Nils; Rose, Christine R.; Ullah, Ghanim (Frontiers in Cellular Neuroscience, 2023)
Emerging evidence indicates that neuronal activity-evoked changes in sodium concentration in astrocytes (Naa) represent a special form of excitability, which is tightly linked to all other major ions in the astrocyte and extracellular space, as well as to bioenergetics, neurotransmitter uptake, and neurovascular coupling. Recently, one of us reported that Naa transients in the neocortex have a significantly higher amplitude than those in the hippocampus. Based on the extensive data from that study, here we develop a detailed biophysical model to further understand the origin of this heterogeneity and how it affects bioenergetics in the astrocytes. In addition to closely fitting the observed experimental Naa changes under different conditions, our model shows that the heterogeneity in Naa signaling leads to substantial differences in the dynamics of astrocytic Ca2+ signals in the two brain regions, and leaves cortical astrocytes more susceptible to Na+ and Ca2+ overload under metabolic stress. The model also predicts that activity-evoked Naa transients result in significantly larger ATP consumption in cortical astrocytes than in the hippocampus. The difference in ATP consumption is mainly due to the different expression levels of NMDA receptors in the two regions. We confirm predictions from our model experimentally by fluorescence-based measurement of glutamate-induced changes in ATP levels in neocortical and hippocampal astrocytes in the absence and presence of the NMDA receptor' antagonist (2R)-amino-5-phosphonovaleric acid.